Qualidade fisiológica e armazenamento de sementes de Myrcianthes pungens (Berg) Legr. - Gibbert, Patrícia (2018)
The irregular production of native tree seeds, makes it important to the conservation of the genetic material available. Myrcianthes pungens has recalcitrant seeds, then the challenge is to preserve the physiological potential by ex-situ methods. It is known that the reduction of respiratory efficiency is a good indicator of the beginning of seed deterioration. The determination of dehydrogenases activity (tetrazolium test (ZT) and measurement of respiratory activity (MRA)) may assist in defining the adequate conditions to maintain the longevity of seeds. The aim was to standardize the ZT methodology. Additionally, the physiological and biochemical behavior of guabiju seeds stored in different packages for up to 10 months was studied. Seeds were collected in Toledo (M1), Pato Bragado (M2) and Marechal Cândido Rondon (M3). The water content (WC) was determined. For ZT standardization, seed preparation and pre-conditioning were tested. The temperatures of 30 and 40 °C and concentrations of 0,50, 0,75, 1,00, 1,25 and 1,50% of tetrazolium salt were tested for 24 hours. In addition, the germination test (GT) was performed. For storage, the seeds were initially evaluated by WC, GT and emergency test (ET). Seeds were stored in cold and dry chamber in plastic, glass and paper containers at initial WC for zero, two, four, six, eight and ten months. For each storage period, the WC, GT, ZT and MRA were carried out. A completely randomized design and non-parametric Friedman analysis were used. Freshly harvested seeds had 39,4, 40,4 and 39,3% WC for M1, M2 and M3. Seeds without imbibition and with tegument did not color, with cut, colored excessively. The percentages of ZT were similar to those of GT. Initially germination was 92, 86 and 85% and emergence 82, 84 and 53% for M1, M2 and M3 respectively. During storage WC kept for seeds stored in glass and plastic and decreased for paper. Germination for seeds stored in the plastic remained high up to ten months. For glass and paper only up to two months. The percentage of dead and non-germinated but viable seeds, speed index and mean germination time, seedling dry mass and mass decreased according to GT for glass and paper and varied for plastic. The ZT indicated viability up to ten, two and four months for plastic, glass and paper respectively. The MRA for paper increased, for glass decreased and for plastic remained with slight variations. The ZT must be performed with preconditioning of the seeds without integument for 24 hours followed by soaking in 0,75% solution of tetrazolium for 24 hours at 30 °C. The plastic was the best storage packaging of the guabiju seeds, maintaining the viability and vigor of the seeds for the period of 10 months. The other packages, maintaining the viability and vigor for only 2 months, and are not recommended for the species.